Manajemen Pembelajaran Bahasa Arab di Madrasah Tsanawiyah Nageri 11 Kabupaten Cirebon - Asep - Kurniawan (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2021)
To realize the objectives of learning Arabic, of course, a good Arabic learning management is needed, so the learning objectives can be achieved as much as possible. This article aimed to reveal more about the management of Arabic language learning at Public Islamic Junior High School 11 Cirebon Regency. This study used a descriptive qualitative research approach. Data collection techniques were observation, interviews and documentation. The results showed that the Arabic learning planning was based on the curriculum that had been prepared by the vice principal of the curriculum, the curriculum development team, and the Arabic teachers. The Arabic language learning was included preliminary, core and closing activities. Evaluation was carried out by the principal to evaluate learning strategies. Evaluation of the content of the material was carried out by the vice principal of the curriculum, the curriculum development team and subject teachers at the end of academic year. Meanwhile, the evaluation of student learning outcomes was carried out by the teacher in written and oral exams. In the implementation of learning, there was supporting factor, namely the qualifications of educators.Â  Meanwhile, the inhibiting factors were students, media and learning methods. The results achieved can be seen from the students' achievements that were already in the sufficient category.